Literasi Kesehatan Melalui Edukasi Cuci Tangan Menggunakan (Waterless Hand Soap) Pada Siswa Paud Karya Bunda Mandiri: Jurnal Literasi Kesehatan - Susanti, Sani; Bangun, Melly Br; Pricilia, Yolanda; Suci, Delli; Ridoansih, Thomas; Ayuning, Vista; Padmawati, Fitri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to educate hand washing movements using (waterless hand soap) as health literacy for early childhood. This research was carried out at Paud Karya Bunda Mandiri with research subjects namely children aged 5-6 years. The approach to this research was to use a qualitative approach. Data collection techniques are through observation, interviews and documentation. The results of the research show that teachers and preschool children can understand the explanation of health literacy through hand washing education using (waterless hand soap). The hand washing movement using (waterless hand soap) is present as a solution in Health literacy in preschool children who are not provided with a place to wash their hands at school